Tradisi Pesta Laut Kago Ago di Buton: Menggali Nilai Religiusitas dan Kearifan Lokal - Lasaiba, M A; Touwe, Sem; Riry, Roberth Berthy (Lani: Jurnal Kajian Ilmu Sejarah dan Budaya, 2024)
This study examines the Kago Ago Sea Festival, a maritime tradition practiced by the Buton community in Southeast Sulawesi, Indonesia. This tradition embodies religious values and local wisdom, reflecting the close relationship between society, nature, and spirituality. Through a series of rituals such as collective prayers and offerings to the sea, the Kago Ago Sea Festival serves to strengthen social solidarity, maintain marine ecosystem sustainability, and express gratitude and reverence to supernatural forces. However, modernization and tourism pose challenges by altering the ritual's meaning and shifting values among younger generations. This research employs an ethnographic method, utilizing participant observation and in-depth interviews to explore the religious, social, and ecological dimensions of the Kago Ago Sea Festival. The findings reveal that this ritual not only functions as a medium for religious expression but also as a social mechanism to maintain environmental balance and strengthen cultural identity. Therefore, efforts to preserve the Kago Ago Sea Festival should consider the underlying spiritual and social values of this practice